2021
DOI: 10.1016/j.jaim.2021.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Screening of anti-microbial, anti-biofilm activity, and cytotoxicity analysis of a designed polyherbal formulation against shigellosis

Abstract: Background Shigellosis is an infectious intestinal disease common in rural communities. In developing countries, shigellosis is caused predominantly by Shigella flexneri and has been determined as a major cause of morbidity and mortality. Objective The study investigates the anti-biofilm, anti-microbial, and anti-shigellosis activity of a designed formulation. Materials and methods The potential of the formulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…53,54 The significant percentage biofilm inhibition exhibited by the EC in all the three sets of extracts' concentrations has pointed to the advantage of polyherbal combination in treating wound infection. 55 The same pattern was reported by Jose et al 54 where they showed a promising percentage of biofilm inhibition of a herbal combination against toxigenic Vibrio cholerae at a relatively lower concentration compared to the individual plants extracts. Different phytoconstituents in herbal combinations have been reported to simultaneously inhibit diverse QS-regulated virulence factors' production.…”
Section: Discussionsupporting
confidence: 70%
“…53,54 The significant percentage biofilm inhibition exhibited by the EC in all the three sets of extracts' concentrations has pointed to the advantage of polyherbal combination in treating wound infection. 55 The same pattern was reported by Jose et al 54 where they showed a promising percentage of biofilm inhibition of a herbal combination against toxigenic Vibrio cholerae at a relatively lower concentration compared to the individual plants extracts. Different phytoconstituents in herbal combinations have been reported to simultaneously inhibit diverse QS-regulated virulence factors' production.…”
Section: Discussionsupporting
confidence: 70%
“…The disruption of the microbial cell to cell communication by oils and plant extracts is due to their various active compounds that mimic the quorum sensing signaling molecules, or may accelerate their degradation (Vattem et al, 2007). The formulation reduces the S. flexneri (67.94%), S. enterica (65.56%), E. coli (51.94%) biofilm formation in comparison with the control, and also possesses anti-QS and antimicrobial properties (Alibi et al, 2020;Koh and Tham, 2011;Singh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirm that the compound inhibiting biofilm will also inhibit quorum-sensing (QS) (Singh et al, 2021). Currently, there is a greater global interest in non-synthetic, natural drugs derived from herbal sources, owing to better tolerance and minimum adverse drug effects.…”
Section: Introductionmentioning
confidence: 99%
“…According to data in the literature, the advancement of the epithelial barrier, increased adhesion to the intestinal mucosa, production of antibacterial substances, competitive exclusion of pathogens, simultaneous suppression of bacterial adhesion, and modulation of the immune system are some of the main mechanisms of action of probiotics [ 87 , 88 , 89 , 90 , 91 ] ( Figure 1 ).…”
Section: Mechanisms Of Action Of Probioticsmentioning
confidence: 99%